2013
DOI: 10.1117/12.2017099
|View full text |Cite
|
Sign up to set email alerts
|

Structural field of K2Al2B2O7-family crystals

Abstract: The known crystal structures of borate compounds with general composition A I 2 M III 2 B 2 O 7 (A I : Na, K, Cs, Rb) have been considered. The structures in space groups P6 3 /m, P-31c, P321 and P2 1 /c have been found depending on cation combination. Criterion k = (r(M III )+r(B)+2r(O))/r(A I ) has been formulated and it controls the formation of trigonal K 2 Al 2 B 2 O 7 (KABO) type structure. The existence of noncentrosymmetric KABO-type borates is possible over the range of k = 2.7 -2.06. This range is pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 25 publications
0
6
0
Order By: Relevance
“…Rare earth ions doped borate compounds as the luminescence materials have been widely investigated, as a result of their low synthetic temperature and good physical and chemical stability. As for the potassium aluminum borate K 2 Al 2 B 2 O 7 (KAB), the powder of KAB was preliminarily studied by Kaduk and Satek at first, and then the crystal of KAB was found to be a new UV nonlinear optical crystal. , Therefore, the crystal growth of KAB and its detail structure were intensively studied due to its easy crystal growth, good chemical stability, and mechanical properties and high UV transparency. Recently, the optical properties of Dy 3+ doped KAB for n-UV excited w-LEDs were reported by Palaspagar et al To the best of our knowledge, the luminescence properties of Eu 2+ doped KAB (KAB:Eu 2+ ) and its potential application in w-LEDs have not yet been reported in the literature.…”
Section: Introductionmentioning
confidence: 99%
“…Rare earth ions doped borate compounds as the luminescence materials have been widely investigated, as a result of their low synthetic temperature and good physical and chemical stability. As for the potassium aluminum borate K 2 Al 2 B 2 O 7 (KAB), the powder of KAB was preliminarily studied by Kaduk and Satek at first, and then the crystal of KAB was found to be a new UV nonlinear optical crystal. , Therefore, the crystal growth of KAB and its detail structure were intensively studied due to its easy crystal growth, good chemical stability, and mechanical properties and high UV transparency. Recently, the optical properties of Dy 3+ doped KAB for n-UV excited w-LEDs were reported by Palaspagar et al To the best of our knowledge, the luminescence properties of Eu 2+ doped KAB (KAB:Eu 2+ ) and its potential application in w-LEDs have not yet been reported in the literature.…”
Section: Introductionmentioning
confidence: 99%
“…These isostructural materials are, however, centrosymmetric (CS) . The centricity of the A 2 Al 2 B 2 O 7 (A=K, Rb, Cs) materials is thought to be correlated with the size of the alkali cation . Centrosymmetry is observed as the size of the alkali cation increases.…”
Section: Figurementioning
confidence: 99%
“…Centrosymmetry is observed as the size of the alkali cation increases. As α‐RABO is CS, it was suggested that NCS β‐RABO would not exist …”
Section: Figurementioning
confidence: 99%
See 2 more Smart Citations